Mural-based revitalization of community reading parks to enhance literacy and community participation in Ambarjaya Village - Effendi, Harris; Murwonugroho, Wegig (Community Empowerment, 2025)
Indonesia's literacy rate remains relatively low, particularly in rural areas. Community Reading Parks (Taman Bacaan Masyarakat or TBMs), as a form of non-formal education, play a strategic role in fostering a culture of literacy. However, many TBMs lack visual appeal, which often results in low reading interest among children and limited community participation. This community service program aimed to revitalize the Asyfa TBM in Ambarjaya Village through a visual arts approach based on murals, a renewal of the book collection, and the development of a wall magazine. The activities were conducted using the Participatory Rural Appraisal (PRA) method. The results demonstrated a significant increase in children's visits, enhanced visual appeal, and greater community participation. The mural approach proved effective in creating an inspiring and inclusive learning space. The program concludes with policy recommendations for local governments to support the replication of similar programs in other TBMs, especially in rural areas.